ASEAN strategies for the prevention of escalating conflict over the Spratly Islands - Kim, Jinwon (2013)
History of human being has been developed with continuous conflicts. Once, particularly, conflict between/among countries develops into armed conflict, it always accompanies with innocent deaths and destructions. In this regards, this research focused on, in terms of armed conflict prevention, conflict of the Spratly Island located in South China Sea, which is one of the most long-term and complex conflicts in Southeast Asia. Particularly, it has studied about how ASEAN has handled the conflict and whether or not it is effective to prevent armed conflict. For analyzing that, the research was guided by the following research questions:what mechanisms have been employed by ASEAN in order not to resort violence?; what strategies has ASEAN used in that mechanisms?; and are these strategies effective to prevent escalating tensions in the Spratly Island? The research was conducted by qualitative case study methodology. Data used in this study was mainly collected from documents; books, journals, newspaper, and ASEAN official documents regarding to the conflict. Findings of the study were obtained by analyzing the documents and categorizing data into similar theme. Based on the methodology, the three main findings are outlined. First, ASEAN has employed four strategies to prevent armed conflict around the Spratly Islands; multilateralism, a limited early warning and early response, confidence-building as preventive diplomacy, and maintaining status quo. Second, these ASEAN strategies were effective until 2006,contributing to prevention of increasing tensions in the region. However, there was little effect in 1990’s because ASEAN finally became a perfect regional organization in 1999 when Cambodia lastly joined in 1999. Finally, since 2007, frequency of events escalating tensions in the area, particularly actions related to military forces, is dramatically increasing. This indicated the need of making up for the weakness in the ASEAN’s strategies. Three contextual causes were identified as follows; Chinese military rapid buildup, the U.S. military presence into the Spratly Islands, and an absence of effective agreement that can restrain and control the detailed actions, military actions in particular, of respective parties which maybe increase tensions. This study concluded that ASEAN’s strategies on the conflict of the Spratly Islands are successful so far because an armed conflict has not been occurred since 1990. Notwithstanding, it is evident that the increasing the frequency of events escalating tensions around the Spratly Islands is a big crisis that ASEAN should be attentive.